2017
DOI: 10.1016/j.comptc.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study on the effect of OH and Cl adsorption on the surface structure of α-Fe2O3

Abstract: Hematite (α-Fe2O3) has been identified as the dominant structure of the outermost layer of the passive film formed on iron surfaces in alkaline environment but chloride has been suggested to play a major role in the depassivation of this passive film under the same conditions. Here we study the effects of OH and Cl adsorption as well as co-adsorption at different coverages on the structure of α-Fe2O3 Fe-terminated (0001) surface using DFT+U. The adsorption of both OH and Cl alters the structure of the surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…E ad decreases by 0.09 eV in the range of OH coverages considered [figure 4(a)] to 2.19 eV for 1/3 ML. This agrees well with recent PBE+U result (2.31 eV [19]). Adsorption energies calculated by using PBE+U+D3, i.e.…”
Section: Oh Adsorptionsupporting
confidence: 94%
See 1 more Smart Citation
“…E ad decreases by 0.09 eV in the range of OH coverages considered [figure 4(a)] to 2.19 eV for 1/3 ML. This agrees well with recent PBE+U result (2.31 eV [19]). Adsorption energies calculated by using PBE+U+D3, i.e.…”
Section: Oh Adsorptionsupporting
confidence: 94%
“…Stability of two hydroxylated, iron and oxygen terminated surfaces has been studied using surface-specific DFT+U approach [18]. The effects of OH adsorption at different coverages on the structure of Fe-terminated α-Fe 2 O 3 (0001) surface was also studied [19]. Calculations of Negreiros et al [20], including the van der Waals correction, of the interaction of very low coverage of water with this surface, showed that a negatively charged surface reduces the energy barrier and enhances substantially the water binding and inhibits water dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Atomistic modeling techniques, such as reactive force field molecular dynamics (ReaxFF-MD) [33][34][35][36][37][38][39][40][41][42] and density functional theory (DFT), [43][44][45][46][47][48] have shown great potential to provide answers to such questions. In particular, ReaxFF-MD has emerged as a simulation framework to investigate reactive processes at spatial scales of nm 2 that can be correlated to physical systems.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice constants for the unit cell of α-Fe 2 O 3 are optimized as a = b = 5.027 Å and c = 13.724 Å (c/a = 2.73) in this study, in good agreement with experimental values (a = b = 5.035 Å and c = 13.747 Å) 34 . The magnetic state for of α-Fe 2 O 3 is applied as antiferromagnetic (+ + − −) based on our previous study 29 . More information regarding properties of α-Fe 2 O 3 and surface structure can be found elsewhere 8,9,29 .…”
Section: Methodsmentioning
confidence: 99%
“…The magnetic state for of α-Fe 2 O 3 is applied as antiferromagnetic (+ + − −) based on our previous study 29 . More information regarding properties of α-Fe 2 O 3 and surface structure can be found elsewhere 8,9,29 .…”
Section: Methodsmentioning
confidence: 99%